“Headship”: Making the Case for Fruitful Equality in a World of Indifferent Sameness and Unbridgeable Difference - McCarthy, Margaret Harper (Religions, 2020)
The article takes up the biblical category of “headship,” one of the “third rails” for Christians in a context dominated by the limited conceptions of equality, especially those assumed by “second wave” and “difference” feminism, viz., that of interchangeable sameness and unbridgeable difference. Headship is easily dismissed as an instance of (bad) cultural influence that spoiled Christianity’s egalitarian beginnings. Less radically, headship is simply avoided, or glossed over with apologetic caveats. Headship is an embarrassment, because it suggests not only exclusive differences—the “head” is not the “body”—but an order between them. Head and body are “subject to each other” in distinct and coordinated ways. In what follows, the author claims that headship is not only not an affront to equality, but its very condition between subjects who belong to each other in a generous relation of reciprocal and fruitful unity and distinction. Moreover, it is the expression of the novelty of Christianity, regarding first of all the nature of God in whom there is an original Head, and a “positive other,” without any hint of subordinationism (inequality). On the contrary, the Father is never absolute, but always already determined by the Son. This original headship then informs the Christian conception of the world, its positivity, even to the point that it can give something to God. Finally, it informs the this-worldly headships (Christ-Church and husband-wife). There, headship counters the status quo, by countering the “body’s” default immanentistic “certainty” about her exclusive life-giving power, enjoining her to acknowledge a transcendent source. It restores equality to the head. For the “head,” it counters the false absolutist image of God, while enjoining him to “radiate” something of which he is first “subject,” to “be involved with,” and determined by, the woman, as a positive other. It restores equality to the body. In sum, the article urges us to turn towards the deepest resources of Christianity, to find therein a more fruitful equality.